FAKTOR-FAKTOR YANG MENDORONG PETERNAK DALAM MEMPERTAHANKAN POLA MANDIRI PADA USAHA AYAM RAS PETELUR DI KECAMATAN MANIANGPAJO KABUPATEN WAJO - Sitti Nurani Sirajuddin; Khaerati Ashadi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2026)
This study aims to identify the factors that motivate farmers to maintain an independent business model in their layer chicken operations in Maniangpajo Subdistrict, Wajo Regency. The study employed a descriptive method involving interviews and a survey. The respondents consisted of 51 layer chicken farmers who applied an independent business model in their layer chicken operations. The data were analyzed using the Delphi method in three stages. Primary data were collected through open-ended and closed-ended questionnaires, then analyzed to identify the most influential factors. The results of the study indicate that the four main factors driving farmers to maintain an independent business model are adequate capital, higher profits, marketing flexibility, and freedom from constraints. In conclusion, higher profits are the dominant factor in encouraging farmers to maintain an independent business model in the layer chicken industry.